Penatalaksanaan Oligodontia pada Anak 14 Tahun dengan Sindrom Ectodermal Dysplasia: Laporan Kasus (Majalah Kedokteran Bandung, 2015)
Ectodermal dysplasia adalah kelainan herediter yang jarang didapatkan, lebih kurang 7.000 kasus di dunia. Pada kelainan ini terjadi gangguan perkembangan struktur organ-organ yang berasal dari lapisan ektodermal seperti rambut, gigi, kuku, dan kelenjar keringat. Dilaporkan kasus sindrom ectodermal dysplasia pada seorang anak perempuan berusia 14 tahun dengan manifestasi klinis berupa oligodontia (kehilangan gigi lebih dari 6 gigi pada rahang atas dan bawah), rambut tipis dan keriting, abnormalitas bentuk kuku kaki, dan gangguan ekskresi keringat. Tujuan perawatan pasien ini adalah mendapatkan fungsi estetik dan pengunyahan pasien yang terganggu akibat tidak terdapat benih gigi permanen, selain itu juga untuk menjaga supaya pertumbuhan rahang tetap berkembang normal. Penatalaksanaan oligodontia berupa pembuatan gigi tiruan lepasan dan mahkota akrilik pada seluruh gigi anterior rahang atas dan bawah. Simpulan yang didapatkan pada pasien ini adalah tercapainya perbaikan  estetika dan pengembalian fungsi pengunyahan serta pemeliharaan pertumbuhan rahang  dapat terjaga dengan baik.  [MKB. 2015;47(4):255–60]Kata kunci: Ectodermal dysplasia, gigi tiruan, oligodontiaOligodontia Management in Children 14 Years with Ectodermal Dysplasia Syndrome: Case ReportAbstractEctodermal dysplasia is a hereditary disorder that is rarely seen with approximately 7000 cases in the world. In this disorder, Ectodermal dysplasia occurs as a developmental disorder of organ structures derived from the ectodermal layer such as hair, teeth, nails, and sweat glands. This is a case report of ectodermal dysplasia in a 14-year-old girl with clinical manifestations of oligodontia (tooth loss, more than 6 teeth on the upper and lower jaw), thin and curly hair, abnormal toenail shape, and impaired excretion of sweat. The purpose of the treatment was to make the patient regains her esthetic and masticatory functions, which were disrupted by the absence of permanent tooth buds, as well as to maintain the normal growth of the developing jaws. Treatment for the patient’s with oligodontia included the use of removable denture in lower jaw and application of acrylic crowns on all upper and lower anterior teeth resulting in improved esthetics and masticatory function. It is concluded that the treatment has been able to improve the esthetics and to return the masticatory function of the patient while maintaining the normal growth of the jaws. [MKB. 2015;47(4):255–60]Key words: Ectodermal dysplasia, oligodontia, prothes DOI: 10.15395/mkb.v47n4.622
Keywords: Ectodermal dysplasia; gigi tiruan; oligodontia